[Houses Under Lava and Ash, Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of houses under lava and ash on Heimaey. White, partially destroyed and distressed houses sit along a dark street and hills of black ash and lava to the right. Cardboard covered the doorways and windows throughout, the doors and window panes gone. The once metal roofs are peeled up and devoid of color.